Influence of different environmental conditions and giberellic acid treatment on flowering time of divergent genotypes of cabbage (Brassica oleracea var. capitata L.) and their F1 hybrids - Adzic, Sladjan; Girek, Zdenka; Pavlovic, Suzana; Zecevic, Bogoljub; Damnjanovic, Jelena; Cvikic, Dejan; Ugrinovic, Milan (Genetika (Beograd), 2020)
In the process of cabbage breeding and seed production, one of the most important characteristics is the time of flowering. In order to investigate the influence of genotype, season and term of sowing on the flowering process, as well as the genetic control of this trait, an experiment was conducted with three genotypes of cabbage N, B and Scc of different geographical origin and different vegetation length, as well as three new F1 hybrids N x Scc , B x Scc and B x N obtained by hybridization between genotypes. The experiment was conducted during three temperature different seasons S1, S2 and S3 (average cold, cold and warm seasons), in three different sowing terms: August 15 (I), September 1 (II) and September 15 (III). During the winter period favorable for vernalization, two treatments with 300 ppm GA3 were performed. A statistically significant influence of all examined factors: genotype, year, sowing term and gibberellin GA3 treatment, on flowering time was determined. AMMI analysis determined the degree of adaptability of genotypes depending on the growing season, sowing terms and GA3 treatment for the trait time of flowering. The highest stability based on ASV values for flowering time was shown by hybrid BxN and its parental component genotypes B and N, while the hybrid Scc x B proved to be the most unstable in terms of flowering time. The pattern of relative expression of the most important flower repressor BoFLC2 gene showed a certain correlation with the flowering time of genotypes. The lowest quantitative expression of this gene was found in genotype B and it had the earliest flowering in all seasons, while genotype N had the highest relative expression of the BoFLC2 locus and the latest flowering.